PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Erwanda, Gusti; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Construction company were one of economic sectors that have vital position in national of economic. It caused construction sector become more difficult in business competition. But in another side construction sector is valueable because it is prices by investor. Investor looked for benefits is need to know about financial report and it give them the information. Thing that they have to know is Profitability ratio.This study is quantitatif descriptive have aims to investigate the effect of ROA, ROE, EPS and NPM partially and simultaneously to 6 construction company’s stock price. So the result of this study was conducted is EPS ratio only is partially have significant effect and ROA, ROE and NPM have no significant effect on stock price while simultaneously ROA, ROE, EPS and NPM have significant effect on stock price.Keywords: ROA, ROE, EPS, NPM, Stock Price